Narrative Literature Review: Inovasi Teknik Rehabilitasi Ekosistem Mangrove di Indonesia, Efektivitas dan Tantangan: Narrative Literature Review: Innovation in Mangrove Ecosystem Rehabilitation Techniques in Indonesia, Effectiveness and Challenges - Doani Anggi Safira; Syifa, Khozanah; Rahmah, Tsamarah Nur (Fakultas Kehutanan Universitas Jambi, 2026)
ABSTRACT Indonesia holds approximately 23% of the world's total mangrove area, making it the country with the largest mangrove extent globally. However, intensive conversion for aquaculture, agriculture, and coastal infrastructure development has resulted in substantial mangrove degradation, with an estimated loss of over 40% of the original mangrove cover over the past five decades. This literature review aims to compile, analyze, and synthesize mangrove rehabilitation techniques implemented across Indonesia from 2020 to 2025. The study applied a Narrative Literature Review (NLR) method using secondary literature indexed in Google Scholar. Results indicate that mangrove rehabilitation in Indonesia encompasses five principal approaches: (1) direct propagule and seedling planting, (2) transplantation techniques, (3) silvofishery-based rehabilitation, (4) permeable structure and bioengineering approaches, and (5) community-based participatory rehabilitation. Successful rehabilitation is contingent on appropriate site selection, hydrological assessment, species-site matching, and sustained post-planting monitoring. The integration of permeable structures to restore hydrological conditions in severely degraded sites has demonstrated promising outcomes, particularly in areas experiencing high wave energy. Community-based approaches showed higher long-term sustainability compared to top-down government programs. Key challenges include high seedling mortality on degraded mudflats, inadequate monitoring protocols, limited financial continuity, and insufficient community capacity building. Future programs should integrate ecological engineering with socio-economic dimensions and employ remote sensing and drone technologies for large-scale monitoring to ensure the long-term success of mangrove ecosystem recovery. Keywords: community-based rehabilitation, Indonesia, mangrove, permeable structure, silvofishery ABSTRAK Indonesia memiliki sekitar 23% dari total luasan mangrove dunia, menjadikannya negara dengan kawasan mangrove terluas di dunia. Namun, konversi intensif untuk tambak, pertanian, dan pembangunan infrastruktur pesisir telah mengakibatkan degradasi mangrove yang signifikan, dengan estimasi kehilangan lebih dari 40% tutupan mangrove asli dalam lima dekade terakhir. Literature review ini bertujuan untuk mengompilasi, menganalisis, dan menyintesis teknik rehabilitasi mangrove yang telah dilakukan di Indonesia dari tahun 2020 hingga 2025. Penelitian ini menggunakan metode Narrative Literature Review (NLR) dengan sumber literatur sekunder yang terindeks di Google Scholar. Hasil kajian menunjukkan bahwa rehabilitasi mangrove di Indonesia mencakup lima pendekatan utama: (1) penanaman langsung propagul dan bibit, (2) teknik transplantasi, (3) rehabilitasi berbasis silvofishery, (4) pendekatan struktur permeabel dan bioengineering, serta (5) rehabilitasi partisipatif berbasis masyarakat. Keberhasilan rehabilitasi bergantung pada pemilihan tapak yang tepat, penilaian hidrologi, kesesuaian jenis tapak, dan pemantauan pasca tanam yang berkelanjutan. Teknik struktur permeabel menunjukkan efektivitas tinggi di areal terdegradasi berat dengan energi gelombang tinggi, sedangkan pendekatan berbasis masyarakat menghasilkan keberlanjutan jangka panjang yang lebih baik. Tantangan utama mencakup tingginya mortalitas bibit, protokol pemantauan yang tidak memadai, keterbatasan pembiayaan, dan pemberdayaan masyarakat yang belum optimal. Program rehabilitasi ke depan perlu mengintegrasikan rekayasa ekologi dengan dimensi sosial-ekonomi serta teknologi pemantauan modern. Kata kunci: Indonesia, mangrove, rehabilitasi berbasis masyarakat, silvofishery, struktur permeabel